2008
DOI: 10.1002/hep.22764
|View full text |Cite
|
Sign up to set email alerts
|

Detection of novel biomarkers of liver cirrhosis by proteomic analysis

Abstract: Hepatic cirrhosis is a life-threatening disease arising from different chronic liver disorders. One major cause for hepatic cirrhosis is chronic hepatitis C. Chronic hepatitis C is characterized by a highly variable clinical course, with at least 20% developing liver cirrhosis within 40 years. Only liver biopsy allows a reliable evaluation of the course of hepatitis C by grading inflammation and staging fibrosis, and thus serum biomarkers for hepatic fibrosis with high sensitivity and specificity are needed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
101
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 42 publications
(42 reference statements)
6
101
2
Order By: Relevance
“…Fibroblasts and epithelial cells express high-mo- lecular-weight (HMW) tropomyosin isoforms TM2, TM3, and TM6 encoded by the TPM1 gene and TM1 encoded by TPM2. While we have not directly studied the role of TPM1 in fibrosis, TPM1 has been reported as stress fibers that are responsible for ECM deposition (13) and epithelial mesenchymal transformation (EMT) (35,58) or a biomarker of liver fibrosis (34,37) and was reported to play an important role in the pathogenesis of endomyocardial fibrosis (6). In the current study, we used the well-characterized TM311 antibody against tropomyosin, which recognizes up to three bands that presumably correspond to tropomyosin isoforms TM2, TM3, and TM6.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts and epithelial cells express high-mo- lecular-weight (HMW) tropomyosin isoforms TM2, TM3, and TM6 encoded by the TPM1 gene and TM1 encoded by TPM2. While we have not directly studied the role of TPM1 in fibrosis, TPM1 has been reported as stress fibers that are responsible for ECM deposition (13) and epithelial mesenchymal transformation (EMT) (35,58) or a biomarker of liver fibrosis (34,37) and was reported to play an important role in the pathogenesis of endomyocardial fibrosis (6). In the current study, we used the well-characterized TM311 antibody against tropomyosin, which recognizes up to three bands that presumably correspond to tropomyosin isoforms TM2, TM3, and TM6.…”
Section: Discussionmentioning
confidence: 99%
“…One notable characteristic of matricellular proteins is that they are nonessential for tissue homeostasis, but their loss is associated with a wide range of changes in remodeling tissues. 12,13 MFAP4 has been associated with remodeling-related disorders, including liver fibrosis, 14 pulmonary airspace enlargement, 15 and atherosclerosis. 16 Furthermore, we recently showed that MFAP4 promotes airway SMC proliferation in experimental asthma, 17 suggesting that similar effects could be relevant for VSMC biology under pathological conditions.…”
mentioning
confidence: 99%
“…• Proteomic studies including immunohistochemistry in LB have targeted cell structure-associated proteins (e.g., actin, tropomyosin, transgelin and human microfibril-associated protein 4) in order to identify biomarkers of liver cirrhosis [65].…”
Section: Functional Liver Tissue Analysis In Lbmentioning
confidence: 99%